2005
DOI: 10.1055/s-2004-830538
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of G-Protein Coupled Receptor Kinase 2 in Cold Thyroid Nodules

Abstract: G-protein coupled receptor kinases (GRKs) have been shown to regulate the homologous desensitization of different G-protein coupled receptors. We have previously demonstrated that the expression of GRK 3 and 4 is increased in hyperfunctioning thyroid nodules (HTNs) and that GRKs 2, 3, 5 and 6 are able to desensitize the TSHR in vitro. Since cold thyroid nodules (CTNs) and HTNs show different molecular and functional properties, different expression patterns of GRKs in these nodules can be expected. The compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…However, the absence of TSH receptor in anaplastic carcinoma also suggests that the increased GRK2 protein is not necessarily linked to TSH receptor signaling in this thyroid cancer subtype. The regulation of GRK2 by TSH in normal thyrocytes agrees with the up-regulation of genes (phosphodiesterases and regulator of G-protein signaling 2, RGS2) involved in negative feedback of TSH-stimulated cAMP accumulation (Van Staveren et al 2006) and with the decreased GRK2 expression observed in pathological thyroid tissues showing a reduced cAMP stimulation (Voigt et al 2005). Furthermore, alterations of GRK2 expression have been reported in other systems with an increase observed in mitogen-activated lymphocytes (De Blasi et al 1995), mouse heart following treatment with b-adrenergic agonist (Iaccarino et al 1998), angiotensin II-stimulated cardiomyocytes (Theilade et al 2002), and a 1 -adrenergic agonist-activated aorta smooth muscle cell line (Ramos-Ruiz et al 2000); while proinflammatory cytokines, such as interleukin 1, interleukin 6, tumor necrosis factor-a or interferon-g, decreased GRK2 expression in human mononuclear leucocytes (Lombardi et al 1999) and in rat smooth muscle cell line (Ramos-Ruiz et al 2000).…”
Section: Discussionmentioning
confidence: 51%
“…However, the absence of TSH receptor in anaplastic carcinoma also suggests that the increased GRK2 protein is not necessarily linked to TSH receptor signaling in this thyroid cancer subtype. The regulation of GRK2 by TSH in normal thyrocytes agrees with the up-regulation of genes (phosphodiesterases and regulator of G-protein signaling 2, RGS2) involved in negative feedback of TSH-stimulated cAMP accumulation (Van Staveren et al 2006) and with the decreased GRK2 expression observed in pathological thyroid tissues showing a reduced cAMP stimulation (Voigt et al 2005). Furthermore, alterations of GRK2 expression have been reported in other systems with an increase observed in mitogen-activated lymphocytes (De Blasi et al 1995), mouse heart following treatment with b-adrenergic agonist (Iaccarino et al 1998), angiotensin II-stimulated cardiomyocytes (Theilade et al 2002), and a 1 -adrenergic agonist-activated aorta smooth muscle cell line (Ramos-Ruiz et al 2000); while proinflammatory cytokines, such as interleukin 1, interleukin 6, tumor necrosis factor-a or interferon-g, decreased GRK2 expression in human mononuclear leucocytes (Lombardi et al 1999) and in rat smooth muscle cell line (Ramos-Ruiz et al 2000).…”
Section: Discussionmentioning
confidence: 51%
“…The expression of GRK 2,3,5, and 6 can desensitize the TSHR in vitro . GRK 2 expression was found to be decreased in cold thyroid nodules when compared to tissue surrounding the nodules [55]. …”
Section: Molecular Signaling Via Plasma Membrane Receptors In Tcmentioning
confidence: 99%